Pseudomonas aeruginosa outbreak in a pediatric oncology care unit caused by an errant water jet into contaminated siphons - Rudolph, Henriette; Geginat, Gernot; Dürken, Matthias; Schroten, Horst; Tenenbaum, Tobias (The pediatric infectious disease journal, 2012)
We analyzed an outbreak of invasive infections with an exotoxin U positive Pseudomonas aeruginosa strain within a pediatric oncology care unit. Environmental sampling and molecular characterization of the Pseudomonas aeruginosa strains led to identification of the outbreak source. An errant water jet into the sink within patient rooms was observed. Optimized outbreak management resulted in an abundance of further Pseudomonas aeruginosa infections within the pediatric oncology care unit.
Gesehen am 25.06.2015